2016
DOI: 10.1080/15226514.2016.1207604
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of heavy metals accumulation by spontaneous vegetation: Screening for new accumulator plant species grown in Kettara mine-Marrakech, Southern Morocco

Abstract: The present paper aims to perform a screening of native plants growing in Kettara mine-Marrakech (Southern Morocco) for its phytoremediation. Plants and soil samples were collected and analyzed for Pb, Zn, Cu and Cd concentrations at several sites in the mine. The results showed that the soil in the vicinity of Kettara mine is deficient in major elements and contain toxic levels of metals. Spontaneously growing native plants were botanically identified and then classified into 21 species and 14 families. Signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“…( Asteraceae ) is considered to be well adapted to water‐stressed environments, such as arid areas, and even a Saharian bio‐climate, and is known for its robust production of seeds (achene; de Waal, Anderson, & Ellis, 2016). Finally, P. harmala L. and A. horridus L., belonging respectively to the Zygophyllaceae and Asparagaceae families, are local species characterized by their tendency to survive in the local environment (Midhat et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…( Asteraceae ) is considered to be well adapted to water‐stressed environments, such as arid areas, and even a Saharian bio‐climate, and is known for its robust production of seeds (achene; de Waal, Anderson, & Ellis, 2016). Finally, P. harmala L. and A. horridus L., belonging respectively to the Zygophyllaceae and Asparagaceae families, are local species characterized by their tendency to survive in the local environment (Midhat et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Naturalized (Dobignard, 2011) Spontaneous (Fennane et al, 2014) Spontaneous (Fennane et al, 1999) Spontaneous ( and Asparagaceae families, are local species characterized by their tendency to survive in the local environment (Midhat et al, 2017).…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…They can be used in phytoextraction. 19,8 The soil factors such as total metal concentration and pH are able to change soil heavy metal concentrations and indirectly effect metals concentrations in the plant [20]. It has been reported that soil pH has a significant effect on bioavailability of metals and plant uptake increases as soil pH decreases .…”
Section: Resultsmentioning
confidence: 99%
“…5 Halocnemum strobilaceum and Hammada scoparia and their ability to remediate heavy metal which contaminates soils in different places in the world have been studied. [6][7][8]…”
Section: Introductionmentioning
confidence: 99%